Building a foundation in self‐awareness: Genetic counseling students' experiences with self‐care, reflection, and mindfulness. Issue 3 (2nd December 2021) - Bulmer, Laura; Stanley, Christy; Loffredo, Lauren; Mills, Rachel; Doyle, Lauren
Abstract: Stress and anxiety are significant concerns for practicing genetic counselors as well as genetic counseling students and can have downstream effects on patient care. Prior research suggests graduate‐level training in self‐awareness practices such as self‐care, reflection, and mindfulness could have lasting effects for genetic counselors, their patients, and the profession as a whole. This mixed‐methods study assessed self‐awareness among 154 genetic counseling graduate students using the Self‐Reflection and Insight Scale (SRIS), the Mindfulness Attention Awareness Scale (MAAS), and self‐described experiences with self‐awareness practice. Genetic counseling students had significantly lower mean scores on the MAAS and the Insight subscale of the SRIS compared with other health professionals, indicating that genetic counseling students have lower levels of mindfulness and may lack insight into their thoughts and feelings. After starting genetic counseling graduate programs, students were more likely to reduce participation in active self‐awareness practices such as physical activity and mental health counseling. Most students reported having structured practice in self‐care ( n  = 97, 63%), reflection ( n  = 125, 81.2%), and mindfulness ( n  = 77, 50%) as a part of their training programs. Second‐year genetic counseling students reporting mindfulness practices had significantly higher scores on the Insight subscale of the SRIS than those who did not, indicating that students engaged in mindfulness practice are better able to understand their thoughts, feelings, and behavior. The majority of students reported benefitting from structured practice in self‐care ( n  = 63, 64.9%), reflection ( n  = 101, 80%), and mindfulness ( n  = 54, 70.1%). Open‐ended responses regarding students' perceived benefits and limitations of structured practice were analyzed for recurrent themes. Students reported improved self‐awareness which enhanced their counseling relationships during clinical rotations. However, they also perceived that implementation of self‐awareness practices may have been inconsistent. Findings from this study have implications for integrating self‐awareness practices into genetic counseling graduate curriculum.